Computer Games and Software Engineering - Cooper, Kendra M. L; Scacchi, Walt (Chapman & Hall/CRC Innovations in Software Engineering and Software Development Series, 2015)
This book is an ideal reference for software engineers, developers, and researchers. It explores game programming and development from a software engineering perspective, presenting a collection of emerging research on the interaction between two traditionally distinct fields-games and software engineering. Featuring contributions from leading experts in software engineering, the text covers topics such as HALO (Highly Addictive, sociaLly Optimized) software engineering, multi-player outdoor smartphone games, gamifying sports software, and artificial intelligence in games. It also discusses the use of games in software engineering education.